Winged Messengers, Feathered Beauties and Beaks of Divine Wisdom: The Role of Birds in Hindi-Urdu Allegorical Love Stories - Dahnhardt, Thomas (Religions of South Asia, 2013)
This article intends to investigate the role played by different kinds of birds in the narrative scheme of the mediaeval love romance (premakhyan or mathnawi), a literary genre used by Indian Sufi poets aimed at conveying an esoteric message through the allegorical language of war and love. Although the principal actors of these poems are human, the functional role played by different animals such as birds (e.g. parrot, peacock, red-finch etc.) appears both as symbolically illustrative and intrinsically didactic. Works such as the Padmavat of Malik Muhammad Jayasi and the Madhumalati of Sayyid Manjhan Rajgiri are credited with successfully charging the adopted imagery and figurative language of their native Indian environment with the sophisticated teachings of Islamic esotericism (Sufism). The role of birds emerging from these works will be illustrated by and compared against their description in the literary productions of the Deccan where the mathnawi, an important literary genre imported from Persia, featured as one of the predominant expressions of early Urdu literature. The aim of the investigation is to show how through the channel of animal characters, the cross-cultural symbiosis operated in the Indo-Islamic environment appears through the language of symbolism that demonstrates the potential of unification inherent in the realm of imagination